Shifting Contribution of Climatic Constraints on Evapotranspiration in the Boreal Forest - Tongxin Wang; Hongyan Zhang; Jianjun Zhao; Xiaoyi Guo; Tao Xiong; Rihan Wu (Earth's Future, 2021)
Abstract The global evapotranspiration (ET) shows an increasing trend with global warming in recent decades, while ET variation in different regions is still uncertain. Boreal forest ecosystem, as one of the most sensitive regions to climate change, are still poorly understood due to the sparse observation and the changing of ET in the boreal forest has been covered up for lower values compared to lower‐latitude regions. Based on the PT‐JPL model, we estimated the ET in the boreal forest during 1982–2015. The annual ET showed an increasing trend (0.5073 mm year−1). Seventy percentage of the boreal forest area is increasing which mainly occurred in Central Canada, Alaska, Central Siberia and Northern Europe, while 24% is decreasing, which occurred in the southern Siberia, Northern Mongolia and Northern Canada. The quantification of basic climatic factors shows that atmospheric demand is the main factor with an increasing trend which is accordance with the (a) increasing temperature; (b) annual precipitation is increasing providing increasing water supply for boreal forest. Factorial experiments were also conducted and showed that the climatic constraints that contribute mainly to ET have gradually shifted from net radiation to moisture restriction in the boreal forest. The moisture control tendency indicated that ET in the boreal forest was gradually controlled by humidity rather than energy, suggesting a limited water supply and an intensifying water cycle in the boreal forest.